USP28 facilitates pancreatic cancer progression through activation of Wnt/β-catenin pathway via stabilising FOXM1 - Leifeng Chen; Zheng Xu; Qing Li; Qian Feng; Cihua Zheng; Yunyan Du; Rongfa Yuan; Xiaogang Peng (Cell Death and Disease, 2021)
Abstract Ubiquitination is an important post-translational modification that can be reversed by a family of enzymes called deubiquitinating enzymes (DUBs). Ubiquitin-specific protease 28 (USP28), a member of the DUBs family, functions as a potential tumour promoter in various cancers. However, the biological function and clinical significance of USP28 in pancreatic cancer (PC) are still unclear. Here, we showed that PC tumours had higher USP28 expression compared with that of normal pancreatic tissues, and high USP28 level was significantly correlated with malignant phenotype and shorter survival in patients with PC. Overexpression of USP28 accelerated PC cell growth, whereas USP28 knockdown impaired PC cell growth both in vitro and in vivo. Further, we found that USP28 promoted PC cell growth by facilitating cell cycle progression and inhibiting apoptosis. Mechanistically, USP28 deubiquitinated and stabilised FOXM1, a critical mediator of Wnt/β-catenin signalling. USP28-mediated stabilisation of FOXM1 significantly promoted nucleus β-catenin trans-activation, which in turn led to the activation of the Wnt/β-catenin pathway. Finally, restoration of FOXM1 expression abolished the anti-tumour effects of USP28-silencing. Thus, USP28 contributes to PC pathogenesis through enhancing the FOXM1-mediated Wnt/β-catenin signalling, and could be a potential diagnostic and therapeutic target for PC cases.